2015
DOI: 10.1097/md.0000000000001543
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Tooth Loss, Body Mass Index, and All-Cause Mortality Among Elderly Patients in Taiwan

Abstract: To date, the effect of tooth loss on all-cause mortality among elderly patients with a different weight group has not been assessed. This retrospective cohort study evaluated the data obtained from a government-sponsored, annual physical examination program for elderly citizens residing in Taipei City during 2005 to 2007, and follow-up to December 31, 2010. We recruited 55,651 eligible citizens of Taipei City aged ≥65 years, including 29,572 men and 26,079 women, in our study. Their mortality data were ascerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 41 publications
6
33
0
1
Order By: Relevance
“…In a study of 21,700 elderly Japanese, tooth brushing and regular dental visits were associated with survival after controlling for age, sex, education level, smoking, drinking, and medical history. 26 Other studies have found an association between tooth loss and overall mortality in Danish, 27 Taiwanese, 28 Scottish, 29 French 30 and Chinese populations. 31 The mechanism is unclear and it has been suggested that markers of oral health such as tooth loss, visits to the dentist, and tooth brushing may serve as a proxy for life and health stressors that can affect mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 21,700 elderly Japanese, tooth brushing and regular dental visits were associated with survival after controlling for age, sex, education level, smoking, drinking, and medical history. 26 Other studies have found an association between tooth loss and overall mortality in Danish, 27 Taiwanese, 28 Scottish, 29 French 30 and Chinese populations. 31 The mechanism is unclear and it has been suggested that markers of oral health such as tooth loss, visits to the dentist, and tooth brushing may serve as a proxy for life and health stressors that can affect mortality.…”
Section: Discussionmentioning
confidence: 99%
“…reported that tooth loss was positively associated with cognitive decline . The effect of tooth loss on body mass index and all‐cause mortality has also been demonstrated among elderly citizens in Taiwan . In a Finnish population‐based survey of over 8,000 persons with 13 years of follow‐up data, Liljestrand et al .…”
Section: Introductionmentioning
confidence: 98%
“…A number of prospective studies have found an association between tooth loss and all-cause mortality, cardiovascular and cancer mortality [5][6][7][8][9][10][11]. Wearing dentures may reduce the mortality in older adults [7,12,13].…”
Section: Introductionmentioning
confidence: 99%